Fabrication of Ti from a blend of Ti and TiH2 powders via powder metallurgy processing. Issue 15 (18th November 2019) - Sharma, Bhupendra; Shogo, Yamada; Kawabata, Mie; Vajpai, Sanjay Kumar; Ameyama, Kei
ABSTRACT: Cost-effectiveness, simple processing, and high performance are crucial factors for Ti and its alloys development. The high cost of Ti and its alloys comes from both starting materials and complex fabrication and/or machining processes which could be controlled using low-cost starting materials and appropriate near-net-shape fabrication techniques. In this study, the low-cost Ti is prepared, from a mixture of pure-Ti and TiH2 powders, via a powder metallurgy route consisting mechanical milling (MM) followed by dehydrogenation, and subsequent compaction through Spark Plasma Sintering (SPS). The MM mixture of Ti and TiH2 was dehydrogenated at 1073 K, prior to sintering, for various time periods up to 10.8 ks. The microstructural evolution caused by different dehydrogenation time and its effect on the mechanical properties has been investigated. The microstructure of sintered Ti consists of controlled bimodal type acicular α and δ-hydride phases. Consequently, the bimodal-type Ti prepared from a blend of pure-Ti and TiH2 powders exhibited a superior strength of up to 675 MPa, which is higher than that of the Ti prepared by solely pure-Ti powder.